2006
DOI: 10.1021/ja0612403
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Self-Assembly of Core−Shell Organosilicon Microcapsules within a Microfluidic Device

Abstract: The preparation of hierarchically structured organosilicon microcapsules from commercially available starting materials is described. Using a microfluidic device, an emulsion of dichlorodiphenylsilane is formed in a continuous phase of aqueous glycerol. The silane droplets undergo hydrolysis, condensation, and crystallization within minutes to form self-assembled, core-shell microcapsules. The microparticles have been characterized with light and electron microscopy, nuclear magnetic resonance spectroscopy (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 52 publications
4
69
0
1
Order By: Relevance
“…Prior work in our group using reactive silicon chlorides revealed that the continuous phase must have a viscosity sufficient to enable droplet production and just enough water to enable condensation. Too much water causes the condensation reaction to occur rapidly and directly at the disperse phase/continuous phase junction, leading to clogging of the device [27]. A continuous phase of 80 % glycerol/water provides the high viscosity (η = 60 mPa s) [27] and at the same time reduces the concentration of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work in our group using reactive silicon chlorides revealed that the continuous phase must have a viscosity sufficient to enable droplet production and just enough water to enable condensation. Too much water causes the condensation reaction to occur rapidly and directly at the disperse phase/continuous phase junction, leading to clogging of the device [27]. A continuous phase of 80 % glycerol/water provides the high viscosity (η = 60 mPa s) [27] and at the same time reduces the concentration of water.…”
Section: Resultsmentioning
confidence: 99%
“…Too much water causes the condensation reaction to occur rapidly and directly at the disperse phase/continuous phase junction, leading to clogging of the device [27]. A continuous phase of 80 % glycerol/water provides the high viscosity (η = 60 mPa s) [27] and at the same time reduces the concentration of water. Though other continuous phases may provide sufficient properties, the low cost of glycerol makes this system attractive.…”
Section: Resultsmentioning
confidence: 99%
“…Syringes, syringe pumps and a UV source are also needed like in the case of PDMS and glass capillary setups. In this device, chip preparation is avoided and even highly monodisperse double emulsions [189] can be prepared together with particles [190]. Later, Du Prez et al reported [191] that the bending of the discrete phase needle transformed the device from a T-junction to a co-flow geometry (Fig.…”
Section: Types Of Microfluidic Devicesmentioning
confidence: 99%
“…We and others have demonstrated the utility of simple devices for the formation of droplets and microcapsules from reactive precursors [25][26][27][28]. While using tubing and T-junctions provides an uncomplicated alternative to chip-based devices, the approach also enables rapid device reconfiguration that can offer new capabilities.…”
Section: Introductionmentioning
confidence: 99%